Linking international standards of education for the professional training of public accountants and internal control for family businesses in Latin America - Huacca-Incacutipa, Ronald (2022)
The objective of this work is to understand if the accounting study programs of the main Latin American universities consider content oriented to the management of Internal Control in family businesses, in compliance with the suggestions made in the International Education Standards (NIE) for the formation of the public accountant.A review and analysis of the literature was carried out, developing a descriptive theoretical research, where the results indicate that 62.5% of the main Latin American universities develop between one to three subjects directly linked to Internal Control in their accounting study programs. In the same way, studies carried out in the region indicate that the adoption of the NIE is relatively low and at the same time highlight the importance of comprehensive training in the future public accountant, which highlights the need to strengthen these skills in the region's universities.